2009
DOI: 10.1099/mic.0.030643-0
|View full text |Cite
|
Sign up to set email alerts
|

A peroxiredoxin from Mycoplasma hyopneumoniae with a possible role in H2O2 detoxification

Abstract: Mycoplasma hyopneumoniae is the causative agent of porcine enzootic pneumonia, which affects pig farms worldwide, causing heavy economic losses. In the infection process, this bacterium is exposed to reactive oxygen species (ROS) from its own metabolism or generated by the host as one of the strategies used to neutralize the pathogen. Although the presence of classical antioxidant enzymes would be expected in M. hyopneumoniae, important genes directly related to protection against ROS, such as superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The number of P97 and P146 pI isoforms observed in these strains was also distinct, which denotes differences in post-translational processing. Two proteins were identified that showed overexpression in the J strain: 1) P216, an adhesin; and thiol peroxidase (TPx, reannotated as a peroxiredoxin [18]), an oxidative stress-related protein described as a virulence factor for other pathogenic bacteria [19,20]. …”
Section: Resultsmentioning
confidence: 99%
“…The number of P97 and P146 pI isoforms observed in these strains was also distinct, which denotes differences in post-translational processing. Two proteins were identified that showed overexpression in the J strain: 1) P216, an adhesin; and thiol peroxidase (TPx, reannotated as a peroxiredoxin [18]), an oxidative stress-related protein described as a virulence factor for other pathogenic bacteria [19,20]. …”
Section: Resultsmentioning
confidence: 99%
“…In the absence of H 2 O 2 -degrading enzymes in mycoplasmas, such as catalase or superoxide dismutase, H 2 O 2 could potentially diffuse freely outside of the mycoplasma cells even if its diffusion is known to be limited (Bienert et al, 2007). A peroxiredoxin, belonging to a family of antioxidant enzymes (EC 1.11.1.15) able to reduce H 2 O 2 , was identified in Mycoplasma hyopneumoniae (Machado et al, 2009). Orthologs have been identified in other mycoplasmas, including species of the “ Mycoplasma mycoides cluster” such as Mmc strain GM12 (MMCAP2_0054), Mmc strain 95010 (MLC_0500), Mmm strain PG1 (MSC_0053), but no precise function in cell detoxification has been proposed in these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Biological characteristics of certain nucleases in mycoplasmas.Certain mycoplasma can also express various antioxidant enzymes including methionine sulfoxide reductase (MsrA), organic hydroperoxide reductase (Ohr), osmotically inducible protein C (OsmC), superoxide dismutase (SOD), catalase, ClpB, thioredoxin reductase, thiol peroxidase, and peroxiredoxin[85,124,[143][144][145][146]. These enzymes can effectively protect mycoplasmas from oxidative damage imposed by the host, and significantly increase their survival in the host.…”
mentioning
confidence: 99%